Laica as a Cultural Identity of the Moronene People in Kampo Laea Hukaea, Bombana Regency, Southeast Sulawesi, Indonesia - Hamasi, Adriyawan Jarsul; Subroto, T. Yoyok Wahyu (Universitas Negeri Yogyakarta, 2025)
The rapid advancement of technology, particularly in the field of building materials, has significantly influenced contemporary residential construction practices. Many people today prefer using manufactured materials over traditional local ones due to their practicality, availability, and perceived modernity. This trend is also evident among the Moronene tribe, one of the indigenous communities in Southeast Sulawesi. Over time, the Moronene people have gradually abandoned the use of local materials that once formed an integral part of their cultural heritage. This shift has led to a growing detachment among younger generations, who are becoming less familiar with traditional architectural knowledge—posing a threat to the authenticity and identity of the Moronene tribe. This study aims to explore the spatial characteristics of traditional Moronene houses in Kampo Laea Hukaea. Utilizing a qualitative method with an inductive approach, data were collected through direct field observations, with guidance from a gatekeeper to ensure culturally appropriate case selection. Findings from the study reveal that Moronene houses exhibit a linear spatial arrangement from front to back. The layout typically consists of three main sections: the patande or laica irai (front house), the botono (main house), and the dapura or laica ibungku (back house). The patande serves not only as a space for daily household activities but also as a venue for cultural events, such as meparamesi, a ceremonial stage in the traditional Moronene wedding. This dual function highlights the room’s cultural significance. The botono, located at the center of the house, is considered the core space for cultural life. It hosts various traditional ceremonies, including mosere wuu (traditional hair-cutting ritual), kawi’a (traditional wedding ritual), mate’a (mourning ritual), and mobasa-basa (traditional thanksgiving ritual), making it the cultural and communal heart of the home. At the rear lies the dapura, which supports both domestic functions and ritual preparations. Activities in this space include ceremonial bathing and organizing essential items for traditional events, reinforcing its role in preserving cultural practices. These three spatial divisions are consistently found across multiple homes in Kampo Laea Hukaea, indicating their significance as defining features of Moronene residential architecture. Despite the increasing adoption of modern construction materials, these traditional spatial patterns continue to reflect and preserve the cultural values of the Moronene community.